2003
DOI: 10.1128/jb.185.8.2555-2562.2003
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary Relationships among Strains of Mycobacterium tuberculosis with Few Copies of IS 6110

Abstract: Molecular typing ofMycobacterium tuberculosis by using IS6110 shows low discrimination when there are fewer than five copies of the insertion sequence. Using a collection of such isolates from a study of the epidemiology of tuberculosis in London, we have shown a substantial degree of congruence between IS6110 patterns and both spoligotype and PGRS type. This indicates that the IS6110 types mainly represent distinct families of strains rather than arising through the convergent insertion of IS6110 into favored… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 50 publications
2
33
0
Order By: Relevance
“…Spoligotyping seems to be both sensitive and specific for the Beijing family and is also easily comparable between different studies. IS6110 fingerprinting can also be used to detect this genotype family with results that correlate closely with the spoligotyping technique (6). In this study, 6.4% of the strains belonged to Beijing family (Table 1).…”
Section: Discussionmentioning
confidence: 92%
“…Spoligotyping seems to be both sensitive and specific for the Beijing family and is also easily comparable between different studies. IS6110 fingerprinting can also be used to detect this genotype family with results that correlate closely with the spoligotyping technique (6). In this study, 6.4% of the strains belonged to Beijing family (Table 1).…”
Section: Discussionmentioning
confidence: 92%
“…The index 1 − S has been used in molecular epidemiology to measure how well a genetic marker discriminates strains (Hunter and Gaston, 1988;Dale et al, 2003). We remark that both S and C H can be used to measure the genetic homogeneity of a set of pathogenic genotypes (though we could not find examples in the literature).…”
Section: Diversity Measures From Ecological Studiesmentioning
confidence: 89%
“…[24] The bacterial pellet was resuspended in 180 ul buffer ATL (supplied in QIAamp Tissue Kit, QIAGEN GmbH, Hilden, Germany). The extraction of TB DNA was performed according to QIAGEN kit protocol.…”
Section: Dna Extractionmentioning
confidence: 99%
“…[20] The reason for widely used IS6110 in PCR tests is the presence of its multiple copies in M. tuberculosis complex genome which is believed to confer higher sensitivity [21,22,23]. However, few studies from different geographical regions of the world have reported that some clinical isolates have either a single copy or no copy of IS6110 which leads to false negative results [24,25]. For avoiding the contamination during amplification and increasing the sensitivity, new approaches such as nested PCR (two step amplification) [26,27] and multiplex PCR (amplification of two or more gene targets simultaneously) [28,29,30,31] have been exploited for EPTB diagnosis.…”
Section: Introductionmentioning
confidence: 99%